Factors Related to Safety Riding Behavior of Students at the Graha Medika Institute of Health and Technology, Kotamobagu - Besse Rismayani; Hairil Akbar; Sarman Sarman; Christien Gloria Tutu; Anggi Mokoagow (Sean Institute, 2025)
Traffic accidents are a global problem that has occurred alongside the shift in disease patterns from infectious to non-communicable diseases. The number of deaths caused by accidents has reached 1.35 million annually, 90% of which occur in developing countries, which have only 54% of the world's vehicles. This study aims to determine the factors related to driving safety behavior (safety reading) among students at the Graha Medika Institute of Health and Technology, Kotamobagu. The type of research used is analytical with a cross-sectional research design. This study was conducted at the Graha Medika Institute of Health and Technology, Kotamobagu, and the population was 583 students. The sample size in this study consisted of 100 students and the sampling technique used simple random sampling. Data analysis used the chi-square test. The findings show that SIM ownership (p= 0.001), attitude (p= 0.033), peer role (p= 0.033) are related to safe riding behavior and knowledge (p= 0.311) has no relationship to safe riding behavior in students. Driving safety behavior among students is significantly influenced by factors such as driving license ownership, attitudes, and the role of peers, while knowledge alone does not guarantee safe driving practices.